Some issues of studying the activities of Czech musicians in Serbia in the 19th century - Gajić, Milica (Muzikološki zbornik, 2009)
The main object of this paper, dedicated to the issue of studying Czech musicians in Serbia in 19th century, is to point to the dilemmas and their solutions in the musicological research carried out so far. Particular attention was paid to less widely known and rarely presented data on versatile activites of Czech musicians.
Keywords: 19.st.; češki glasbeniki; glasbena migracija; Serbia; Srbija